Correlation of ICDAS-LAA and ORA test for caries risk assessment: A cross-sectional study - Pradeep Daniel Gainneos; Mallika Selvam; Suresh Kumar Vasaviah; Ramesh Krishnan (Wolters Kluwer Medknow Publications, 2019)
Background: Dental caries is the most common chronic disease of children aged 6-11 years. The International Caries Detection and Assessment System-Lesion Activity Assessment (ICDAS-LAA) is a precise tool for the clinical assessment of dental caries by visual appearance, tactile feeling, and potential for plaque accumulation. Ora test is a chairside tool to estimate the ability of acid produced by bacteria to cause demineralization, in a suitable environment. Aim of this study is to correlate ICDAS-LAA and Ora test in assessing the caries risk of a patient on the dental chair. Materials and Methods: A total of 60 school children aged between 6 and 9 years were included in the study. Of 60 children, 30 (Group A) were caries free and 30 (Group B) had decayed missing extraction, filled (DMF) score of 1-3. All the children were initially subjected to ICDAS-LAA scoring, which was assessed by one examiner followed by chairside Ora test performed by another examiner. Results: Statistical analysis was done using Pearson correlation test, and a negative linear relation was found between the time taken for color change in Ora test and ICDAS-LAA scores. Conclusion: A direct correlation exists between ICDAS-LAA scores and Ora test, which shows that microbial activity correlates well with lesion activity.